Effect Of Rejected Watermelon Substitution On The Quality Of Choux Paste - Ananda, Annisa Tria; Anggraini, Ezi; Faridah, Anni; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research is motivated by the low utilization of watermelon rejected. Discarded watermelon is a watermelon with a small size or commonly called sub grade fruit with criteria outside the grade including size, shape, color, appearance of imperfect or damaged fruit. Watermelon contains substances that are useful for the body and has a high water content. One of the utilization of watermelon rejected can be used in the innovation of eclairs (Choux Paste). This study aims to analyze the effect of 25%, 50% and 75% watermelon substitution on the quality of color, shape, texture, aroma and taste of the choux paste produced. The type of research used in this research is pure experiment (True Experiment) with the research design used is a complete randomized design (RAL) with 3 repetitions. The type of data used is primary data obtained directly from 3 limited panelists by filling out the organoleptic test format. For hypothesis testing, this study uses analysis of variance (ANOVA) test, if different will be tested with Duncan Multi Ranges Test (DMRT) test. Based on the results of the organoleptic test and continued with the analysis of variance (ANOVA) test, it shows that there is a significant effect on the quality of brown orange color, hollow texture quality, watermelon fragrant aroma quality and watermelon sweet taste quality. There is no significant difference in the shape quality of eclairs with watermelon substitution. From this statement it can be concluded that the indicators of color, texture, aroma and taste Ho is accepted because f count < f table. While on the quality of the shape Ho is rejected because f count > f table. The best research results on the substitution of watermelon rejected on the quality of eclairs are in treatment 2, namely the use of 50% watermelon rejected.